2014
DOI: 10.1111/jocn.12624
|View full text |Cite
|
Sign up to set email alerts
|

Does language ambiguity in clinical practice justify the introduction of standard terminology? An integrative review

Abstract: The introduction of standard terminology concerning patients' functioning will only be successful when clinical practice requires the aggregation and reuse of data from electronic patient records for different purposes, including multidisciplinary decision-making and research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 26 publications
2
8
0
Order By: Relevance
“…This broadly supports Dickerson, Davis and Staplin [15] who suggested that professional groups such as physicians and occupational therapists have a common language within their groups, but the same words do not have the same meaning between different professional groups. Similar observations were also made by Stallinga et al [16] who commented that language ambiguity allows different interpretations of the same word, with the term "trainability" having a different meaning to different professional groups. Therefore, a possible explanation for low levels of agreement for certain therapeutic techniques between different professional groups may be language ambiguity.…”
Section: When We Examined the Agreement Between Clinicians For Cognitive Other Other Active Interventions And Education On Different Catesupporting
confidence: 80%
“…This broadly supports Dickerson, Davis and Staplin [15] who suggested that professional groups such as physicians and occupational therapists have a common language within their groups, but the same words do not have the same meaning between different professional groups. Similar observations were also made by Stallinga et al [16] who commented that language ambiguity allows different interpretations of the same word, with the term "trainability" having a different meaning to different professional groups. Therefore, a possible explanation for low levels of agreement for certain therapeutic techniques between different professional groups may be language ambiguity.…”
Section: When We Examined the Agreement Between Clinicians For Cognitive Other Other Active Interventions And Education On Different Catesupporting
confidence: 80%
“…Many projects that aim to introduce standard terminology in clinical practice are unsuccessful, perhaps because standard terminology is rarely used in clinical practice 7 . A number of opportunities exist to consider how to most effectively implement standardized terminology for AS into clinical practice.…”
Section: Slow Surveillance Unfamiliarity With the Concept 100mentioning
confidence: 99%
“…In these guidelines, AS is primarily recommended for patients with low-risk tumours; however, these guidelines contain various definitions of low-risk prostate cancer, as specified by different combinations of clinical criteria including clinical and pathological characteristics (such as tumour stage, serum PSA levels, biopsy Gleason score, tumour volume and serum PSA density). Furthermore, definitions of disease reclassification and progression differ among published guidelines and multiple criteria for initiation of curative treatment are proposed 6 .Problems resulting from the use of ambiguous language include hindered clinical decision making, particularly in multidisciplinary collaborations, and limited opportunities for research 7 . Moreover, such ambiguity has raised a barrier that hampers exchange of knowledge within and between fundamental domains of research and research groups 8 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…employed computational or statistical analysis, the term "replicability" is interchangeably used with the term "reproducibility" without any justification or clarification (Plesser, 2018). However, the use of ambiguous terminology can be an impediment to the progress of science and can cause mass confusion and more discussions among scientists (Stallinga et al, 2015). According to the review of literature, the most common way to use the term of "reproducibility" was understanding it as an attempt to verify the data analysis of the study by using same data and same methods for yielding the same results (Plesser, 2018).…”
mentioning
confidence: 99%